Optimizing the recovery process of ceramic grade calcium fluoride from hydrofluoric/hexafluorosilicic acid wastewater. (20th January 2022) - Tran, Quynh Thi Phuong; Lin, Po-Hsun
Abstract: Chemical precipitation using calcium salts has been widely applied in hydrofluoric acid wastewater treatment due to its simplicity, flexibility and economy. Coagulants/flocculants are used to improve solid-liquid separation in a fine precipitate of calcium fluoride (CaF2 ). As a result, a large amount of sludge is generated by CaF2 precipitation process. In order to move towards a circular economy, the current study developed an environment-friendly and cost-effective approach to treat concentrated hydrofluoric/hexafluorosilicic acid wastewater (∼117 g F − /L) obtained from an optoelectronic industry in Taiwan and to recover fluoride as the high purity CaF2, as well as to reduce the amount of final waste disposal. The influence of three independent variables, including calcium-to-fluoride molar ratio ([Ca 2+ /F − ], silicon concentration ([Si 4+ ]), and polymer dosage applied, on the purity of recovered CaF2 products, was investigated and optimized by combining response surface methodology (RSM) with central composite design (CCD). The ceramic grade CaF2 of 85.6–87.9% was achieved under the optimum conditions as [Ca 2+ /F − ] of 0.618–0.645, [Si 4+ ] of 1.48 g/L, and polymer concentration of 17.2–17.8 mg/L. The final turbidity, residual fluoride concentration in the supernatants and fluoride removal efficiency were 14.8–16.2 NTU, 62.2–67.6 mg/L and greater than 99%, respectively. The value of R 2 = 0.9498 and adjusted R 2 = 0.9319 indicated an adequate correlation between experimental results and predictions by the quadratic model. In addition, a new insight into the CaF2 purification method has been proposed based on the idea of pH control. Graphical abstract: Image 1 Highlights: Ceramic grade CaF2 recovery was optimized using CCD/RSM. CaF2 product was characterized using SEM, EDX, and XRD. New insight into the CaF2 purification method was presented.